2012
DOI: 10.1002/lt.23414
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells administered after liver transplantation prevent acute graft-versus-host disease in rats

Abstract: Acute graft-versus-host disease is a serious and life-threatening complication of liver transplantation (LT) that occurs in 1% to 2% of liver allograft recipients. It is associated with a high mortality rate, and effective therapies are lacking. In our established rat model, a relative decrease in regulatory T cells (Tregs) was previously shown to be associated with acute graft-versus-host disease after liver transplantation (LT-aGVHD). Mesenchymal stem cells (MSCs) have been used to treat graft-versus-host di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…These effects may be due to a number of reasons. Firstly, MSCs may immunoregulate the functions of host T cells (28)(29)(30) by direct regulation (31,32), where the MSCs change the immune function through direct contact between cells to regulate the ratio changes of T cell subsets, or indirect regulation (33)(34)(35), where MSCs may inhibit the growth and activation of T cells to cause relative changes to the T cell subsets in order to induce a lower T cell response, through the secretion of immune cytokines, including TGF-β 1 , hepatocyte growth factor, and metabolic products, such as prostaglandin E2 or indole-2,3-dioxygenase. Beyth et al (9) indicated that MSCs affected the maturation of normal APCs indirectly to cause T cells to become unresponsive, through the secretion of IL-10 and the inhibition of monocyte IL-12 secretion, ultimately inhibiting immune rejection.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be due to a number of reasons. Firstly, MSCs may immunoregulate the functions of host T cells (28)(29)(30) by direct regulation (31,32), where the MSCs change the immune function through direct contact between cells to regulate the ratio changes of T cell subsets, or indirect regulation (33)(34)(35), where MSCs may inhibit the growth and activation of T cells to cause relative changes to the T cell subsets in order to induce a lower T cell response, through the secretion of immune cytokines, including TGF-β 1 , hepatocyte growth factor, and metabolic products, such as prostaglandin E2 or indole-2,3-dioxygenase. Beyth et al (9) indicated that MSCs affected the maturation of normal APCs indirectly to cause T cells to become unresponsive, through the secretion of IL-10 and the inhibition of monocyte IL-12 secretion, ultimately inhibiting immune rejection.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] They display a number of remarkable properties, such as the tendency to home to sites of injury, the capacity to suppress immune reactions and the ability to aid in the repair and regeneration of damaged tissues. [15][16][17] Accordingly, MSCs have been explored widely for their applications in regenerative medicine and as delivery vehicles for use in gene therapy. 18 In the context of cancer, MSCs are becoming increasingly recognized as important stromal facilitators of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Rats that received donor-or recipient-derived BM-MSCs from day 0 to day 6 after LT (5 × 10 6 MSCs/day) had a significantly longer survival and no typical LT-associated GVHD symptoms, while administration of MSCs after the onset of symptoms was ineffective for treating GVHD. The efficacy of MSC therapy was associated with higher Treg ratios in the peripheral blood [54].…”
Section: Animal Studiesmentioning
confidence: 97%